2019
DOI: 10.1021/acs.iecr.9b00149
|View full text |Cite
|
Sign up to set email alerts
|

Influence of H2, CO, C3H6, and C7H8 as Reductants on DeNOx Behavior of Dual Monoliths for NOx Storage/Reduction Coupled with Selective Catalytic Reduction

Abstract: The effects of feeding hydrogen, carbon monoxide, and propylene as reductants are analyzed in the combined NO x storage and reduction with selective catalytic reduction technology (NSR-SCR), with Pt−Ba/Al 2 O 3 and Pt− Ba−Ce/Al 2 O 3 monoliths as NSR catalysts, and Cu/BETA and Cu/SAPO-34 monoliths as SCR catalysts. Feed streams including CO 2 and H 2 O mimic the real composition of the diesel engine exhaust. Also, the reaction temperature and reductant concentration are analyzed on NO x removal and product dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 72 publications
0
15
0
Order By: Relevance
“…For this reason, it is important to investigate how different reducing agents influence the production of NH 3 and the by-product formation at the outlet of the LNT catalytic bed. Recently, this aspect was investigated by Urrutxua et al [122] by combining Pt−Ba(-Ce)/Al 2 O 3 as the LNT catalyst with the Cu/BETA and Cu/SAPO-34 monoliths as the SCR catalyst. The results showed that H 2 and CO are equally efficient in NO x reduction starting from 300 • C (at lower temperatures, only H 2 is active), while propylene becomes effective at temperatures near 400 • C. However, since NH 3 is mainly produced when H 2 is used as a reductant (also at low temperatures), the beneficial effects of the LNT-SCR combined configuration are very evident in these conditions but less appreciated at higher temperatures with CO and/or propylene.…”
Section: Fundamental Studies On Lnt-passive Scr Combined Systemmentioning
confidence: 99%
“…For this reason, it is important to investigate how different reducing agents influence the production of NH 3 and the by-product formation at the outlet of the LNT catalytic bed. Recently, this aspect was investigated by Urrutxua et al [122] by combining Pt−Ba(-Ce)/Al 2 O 3 as the LNT catalyst with the Cu/BETA and Cu/SAPO-34 monoliths as the SCR catalyst. The results showed that H 2 and CO are equally efficient in NO x reduction starting from 300 • C (at lower temperatures, only H 2 is active), while propylene becomes effective at temperatures near 400 • C. However, since NH 3 is mainly produced when H 2 is used as a reductant (also at low temperatures), the beneficial effects of the LNT-SCR combined configuration are very evident in these conditions but less appreciated at higher temperatures with CO and/or propylene.…”
Section: Fundamental Studies On Lnt-passive Scr Combined Systemmentioning
confidence: 99%
“…Since its discovery hybrid NSR-SCR systems have been subjected to a continuous development. Indeed, different system architectures, catalytic formulations and operation control have been analyzed [108][109][110][111]. However, the NSR formulation in the combined NSR-SCR configuration is usually based on the Pt-model formulation.…”
Section: Perovskite-based Catalysts For Combined Nsr-scr Technologymentioning
confidence: 99%
“…These formulations have already been implemented for NO x emission control in heavy-duty vehicles and some recently in some passenger's cars in Europe, mainly due to high NO x removal efficiency in a wide temperature window discovered with this small pore zeolite structure. Figure 1 shows the NH 3 -SCR behavior of a 4% Cu/SAPO-34 prepared in our laboratory by the solid state ion exchange method [50]. Experiments were carried out with a feed stream composed of 660 ppm NO, 660 ppm NH 3 , 6% O 2 , and Ar to balance.…”
Section: Selective Catalytic Reduction (Scr)mentioning
confidence: 99%
“…The coupling of NSR and SCR catalysts has been rapidly accepted as a potential solution, since its discovery by the Ford Motor company [9,108]. Different catalytic formulations, system architectures, and operation control have been explored [7,8,50,109,110]. The systems based on model NSR formulation and Cu/chabazite-type zeolites emerge as the most efficient combination [111].…”
Section: Nsr-scr Combined Systemmentioning
confidence: 99%